Allergic manifestation 15 years after early intervention with hydrolyzed formulas – the GINI Study. Issue 2 (23rd November 2015) - von Berg, A.; Filipiak‐Pittroff, B.; Schulz, H.; Hoffmann, U.; Link, E.; Sußmann, M.; Schnappinger, M.; Brüske, I.; Standl, M.; Krämer, U.; Hoffmann, B.; Heinrich, J.; et al.
Abstract: Background: Data on the long‐term impact of hydrolyzed formulas on allergies are scarce. Objective: To assess the association between early intervention with hydrolyzed formulas in high‐risk children and allergic outcomes in adolescence. Methods: GINI trial participants ( n = 2252) received one of four formulas in the first four months of life as breastmilk substitute if necessary: partial or extensive whey hydrolyzate (pHF‐W, eHF‐W), extensive casein hydrolyzate (eHF‐C) or standard cow′s milk formula (CMF) as reference. Associations between these formulas and the cumulative incidence and prevalence of parent‐reported physician‐diagnosed asthma, allergic rhinitis (AR) and eczema, as well as spirometric indices and sensitization, were examined using generalized linear models. Results: Between 11 and 15 years, the prevalence of asthma was reduced in the eHF‐C group compared to CMF (odds ratio (OR) 0.49, 95% confidence interval (CI) 0.26–0.89), which is consistent with the spirometric results. The cumulative incidence of AR was lower in eHF‐C (risk ratio (RR) 0.77, 95% CI 0.59–0.99]) and the AR prevalence in pHF‐W (OR 0.67, 95% CI 0.47–0.95) and eHF‐C (OR 0.59, 95% CI 0.41–0.84). The cumulative incidence of eczema was reduced in pHF‐W (RR 0.75, 95% CI 0.59–0.96) and eHF‐C (RR 0.60, 95% CI 0.46–0.77), as was the eczema prevalence between 11 and 15 years in eHF‐C (OR 0.42, 95% CI 0.23–0.79). No significant effects were found in the eHF‐W group on any manifestation, nor was there an effect on sensitization with any formula. Conclusion: In high‐risk children, early intervention using different hydrolyzed formulas has variable preventative effects on asthma, allergic rhinitis and eczema up to adolescence.